The Political and Economic Status of the Chinese Diaspora in Southeast Asia - Yonghao Wang (Евразийская интеграция: экономика, право, политика)
The relevance of the study stems from the Chinese government’s focus on developing cultural, economic partnerships with Asia-Pacific states. It is the Huaqiao who have contributed to this process, for example, there are many investors who balance the flow of money between China and other countries, as well as scholars who share scientific knowledge with Chinese citizens.Aim. Based on the above, the aim of the study is to analyse the current position of the Chinese diaspora in the economic and political spheres of life in Southeast Asia.Tasks. In order to successfully realise the objective, it is necessary to solve the research tasks:to describe the essence of the concept of “diaspora” in the academic literature, as well as its specific features;to consider the role of huaqiao in the formation of China’s external image;to evaluate the degree of Chinese business activity in trade of the countries under consideration;4) to study the degree of Chinese diasporas’ participation in political life of the states of residence.Methods. Analysis and synthesis of literary sources (while studying the concept of “diaspora”), historical method (while describing three main waves of Chinese diaspora migration and studying Chinese settlement in different parts of South-East Asia), descriptive method (while studying the place of Chinese diaspora in political and economic life of South-East Asia) were used as main research methods.Results. The research results have been summarised according to the level of representation of the positive image of the Chinese as a result of the Huaqiao’s economic and political actions.Conclusions. Firstly, about 75% of overseas Chinese, or 28 million people, live in modern Southeast Asian countries.Secondly, within the framework of the business activities of the Chinese diaspora, the most significant factor of influence is the association of Chinese enterprises in the “bamboo network” and expansion of areas of cooperation with each other.Third, the Chinese diaspora has different rights these days depending on the form of government and state structure of the country.